2019
DOI: 10.1590/s1980-220x2018016303486
|View full text |Cite
|
Sign up to set email alerts
|

Impacto das infecções relacionadas à assistência à saúde nos custos da hospitalização de crianças

Abstract: RESUMO Objetivo Avaliar o impacto das Infecções Relacionadas à Assistência à Saúde no custo da hospitalização de crianças. Método Estudo de coorte, prospectivo, quantitativo, envolvendo crianças admitidas nas Unidades de Internação e de Terapia Intensiva Pediátrica de um hospital universitário público. Os dados foram analisados por meio do software SPSS por distribuição de frequências, medidas de tendência central e dispersão. Para todas as análises foi considerado o nível de significância estatística de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 11 publications
0
22
0
10
Order By: Relevance
“…It was evaluated, in the northern region of the state of Paraná, the economic impact of HAI on the cost of hospitalization of children from July to December of 2015. The authors found that the costs of HAI patients during hospitalization were 4,2 times higher than those without it (6) . In Resende, in the state of Rio de Janeiro, a research investigated the total cost of patients in an ICU and found that 38.4% of this amount was assigned to the treatment of HAI patients acquired in the ICU, 35.7% for patients who have already admitted with infection and 25.9% for patients without infection (11) .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was evaluated, in the northern region of the state of Paraná, the economic impact of HAI on the cost of hospitalization of children from July to December of 2015. The authors found that the costs of HAI patients during hospitalization were 4,2 times higher than those without it (6) . In Resende, in the state of Rio de Janeiro, a research investigated the total cost of patients in an ICU and found that 38.4% of this amount was assigned to the treatment of HAI patients acquired in the ICU, 35.7% for patients who have already admitted with infection and 25.9% for patients without infection (11) .…”
Section: Introductionmentioning
confidence: 95%
“…Direct costs are those spent on hospitalization, and indirect costs are the productivity losses for society, due to absenteeism and mortality (5) . In the United States, a total of 1,7 million patients diagnosed with HAIs are estimated annually, of which almost 100.000 evolve to death, resulting in costs of more than U$ 30 billion/year (6) .…”
Section: Introductionmentioning
confidence: 99%
“…A infecção é uma complicação frequente que contribui para as elevadas taxas de morbidade e mortalidade em situações de pós-operatório. No Brasil, as infecções póscirúrgicas representam umas das principais infecções relacionadas à assistência à saúde, com o percentual de 14% a 16%, entre as infecções que acometem pessoas hospitalizadas (ALECRIN, 2019;LEONCIO, 2019;DOS SANTOS, 2018).…”
Section: Introductionunclassified
“…As infecções pós-cirúrgicas são indubitavelmente relevantes para a definição de agravos à saúde, contribuindo para uma maior hospitalização, aumento do custo de assistência e aumento das taxas de reinternação. Para as crianças, essas infecções atuam como um importante fator limitante para a vida, uma vez que elas possuem uma fragilidade imunológica, própria dos extremos da idade (LEONCIO, 2019;.…”
Section: Introductionunclassified
“…Além disso, pode-se dizer que a IH torna-se um fácil caminho para a seleção e disseminação de microrganismos multirresistentes (LEONCIO et al, 2019).…”
Section: Introductionunclassified